Gardens of Things: The Vicissitudes of Disappearance - Starosta, Anita (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2007)
This essay traces the disappearance of the Soviet Union through aesthetical and everyday objects, and through an organization of the ethical and economic values that mark the so-called post-Soviet world. Looking through the different ways historical changes are mediated and made apprehensible, I propose to read Ryszard Kapuscinski's non-fictional account Imperium, Zbigniew Herbert's poems “Elegy for the Departure of Pen, Ink and Lamp” and “The Envoy of Mr. Cogito,” and Krzysztof Kieslowski's film No End (1984). I argue that the vicissitudes of disappearance question notions of historical rupture, making visible the processes of cultural renegotiation and reconstitution.